Designing & Facilitating Collaborative Learning Networks. A toolkit - and Folsom, Amanda (2023)
Collaborative Learning — an approach which brings together people who face common challenges to share knowledge and jointly problem-solve — is a powerful way to support locally-led development and achieve impact. It provides a structured process in which change agents determine priorities, set the learning agenda, work together to identify strategies to address complex challenges, and provide ongoing implementation support to one another. Collaborative Learning — unlike traditional approaches to technical assistance — centers the expertise of local change agents and captures the valuable tacit knowledge of practitioners to advance systems change. This toolkit synthesizes lessons, tips, and tools accumulated from more than a decade of experience designing and facilitating over 20 Collaborative Learning Networks. The lead author was Amanda Folsom, Senior Program Director and Collaborative Learning Practice Lead, Results for Development (R4D). The toolkit benefited from the contributions of many R4D colleagues, including Katie Bowman, Cheryl Cashin, Tanya Jones, Gina Lagomarsino, Agnes Munyua, Maria Jose Pastor, and Abeba Taddese. R4D has not done this alone. The lessons and examples are drawn from our work with many network partners from the Joint Learning Network for Universal Health Coverage (JLN), Linked Immunisation Action Network (Linked), Health Systems Strengthening Accelerator, Strategic Purchasing Africa Resource Center (SPARC), the Primary Health Care Performance Initiative (PHCPI), the Partnership for Evidence and Equity in Responsive Social Systems (PEERSS), and the School Action Learning Exchange (SALEX), to name a few. We are grateful for the thought partnership and support of our partners and funders, including the Bill & Melinda Gates Foundation, Gavi, Hewlett Foundation, Jacobs Foundation, Rockefeller Foundation, USAID, and World Bank.